EFFECTIVENESS OF VILLAGE GOVERNMENT WORK IN POPULATION ADMINISTRATION SERVICES IN KARANGAMPEL VILLAGE BAREGBEG DISTRICT CIAMIS DISTRICT: Array - Nina Kurniawati; Sahadi (JGSRD: Journal of Government Science and Rural Development, 2022)
This research is motivated by the problem of effectiveness of the work of the village government Karangampel Baregbeg District Ciamis which stems from problems in the service of Population Administration, uncertainty about the timing of completion of services, lack of disciplinary level of apparatus in carrying out population administration services, lack of level of accuracy of apparatus in population administration services The purpose of this study is to know the effect work of the Village Government in Population Administration Services in Karangampel Village, Baregbeg District, Ciamis Regency. The method used is descriptive qualitative with data collection techniques that are conducting literature studies, field studies (observations and interviews). While the informants in this study as many as 10 people. Based on the results of the study, it is known that the effectiveness of the work of the village government in the population administration service in Karangampel Village has not been optimal. It can be seen from the existence of some dimensions used as measuring instruments in this study has not been running optimally. The obstacles are the constraints of power outage disruption in the population administration service, the disruption of the network or central server in online data transmission, the number of incoming jobs that make it less focused and thorough so that the work sometimes becomes late, the lack of discipline of village officials sometimes there are still in and out of the office is not in accordance with the schedule.